Pursue A Foreign Foundation Locally. - The, Star (The Star, 2020)
Dear school-leavers, if you have not decided what you wan to do next, a foundation programme may be just what you need. Good news! you may now earn a University of London qualification without going to London. Being a recognized Teaching Centre of University of London in Malaysia. Asia e University offers the London International Programme (IFP) at its SS15 campu. This IFP is an excellent bridge for those who wish to study overseas. The March/April 2020 intake is now open for registration.